The courage to go forward : the power of micro communities - Cordani, David, 1966-; Traum, Dick, 1940- (New York : Morgan James Publishing, 2018)
The Courage to Go Forward shows that individuals need to think differently about creating supportive communities to help each other set and achieve goals, both individually and collectively. Those interested in making a positive impact on society need to consider how to complement societal programs designed for the "average" person with customized approaches tailored to the unique needs and aspirations of every individual. Focused on the inspirational relationship between Cigna, a global health service company, and Achilles International, a nonprofit focused on encouraging disabled people to participate in mainstream athletics, The Courage to Go Forward demonstrates the power and triumph of the human spirit and provides valuable insight into the formation and importance of micro communities. David Cordani, president and CEO of Cigna, and Achilles International founder and president Dick Traum come from very different backgrounds yet share a similar set of passions that eventually brought them together, forming a relationship that has positively impacted communities ranging from inspired employees to thousands of disabled athletes competing at the highest levels.
eBooks on EBSCOhost
Keywords: Courage; Small groups; Communities; Social action; Social responsibility of business; Courage; Petits groupes; Communauté.; Action sociale; Entreprises -- Responsabilité sociale; Leadership; BUSINESS & ECONOMICS; Physical Impairments; HEALTH & FITNESS; SELF-HELP.; Communities; Courage; Small groups; Social action; Social responsibility of business